Gut bacterium Intestinimonas butyriciproducens improves host metabolic health: evidence from cohort and animal intervention studies - Elena Rampanelli; Nadia Romp; Antonio Dario Troise; Jakshana Ananthasabesan; Hao Wu; Ismail Sahin Gül; Sabrina De Pascale; Andrea Scaloni; Fredrik Bäckhed; Vincenzo Fogliano; Max Nieuwdorp; Thi Phuong Nam Bui (Microbiome)
Abstract Background The human gut microbiome strongly influences host metabolism by fermenting dietary components into metabolites that signal to the host. Our previous work has shown that Intestinimonas butyriciproducens is a prevalent commensal bacterium with the unique ability to convert dietary fructoselysine to butyrate, a well-known signaling molecule with proven health benefits. Dietary fructoselysine is an abundant Amadori product formed in foods during thermal treatment and is part of foods rich in dietary advanced glycation end products which have been associated with cardiometabolic disease. It is therefore of interest to investigate the causal role of this bacterium and fructoselysine metabolism in metabolic disorders. Results We assessed associations of I. butyriciproducens with metabolic risk biomarkers at both strain and functional levels using a human cohort characterized by fecal metagenomic analysis. We observed that the level of the bacterial strain as well as fructoselysine fermentation genes were negatively associated with BMI, triglycerides, HbA1c, and fasting insulin levels. We also investigated the fructoselysine degradation capacity within the Intestinimonas genus using a culture-dependent approach and found that I. butyriciproducens is a key player in the butyrogenic fructoselysine metabolism in the gut. To investigate the function of I. butyriciproducens in host metabolism, we used the diet-induced obesity mouse model to mimic the human metabolic syndrome. Oral supplementation with I. butyriciproducens counteracted body weight gain, hyperglycemia, and adiposity. In addition, within the inguinal white adipose tissue, bacterial administration reduced inflammation and promoted pathways involved in browning and insulin signaling. The observed effects may be partly attributable to the formation of the short-chain fatty acids butyrate from dietary fructoselysine, as butyrate plasma and cecal levels were significantly increased by the bacterial strain, thereby contributing to the systemic effects of the bacterial treatment. Conclusions I.  butyriciproducens ameliorates host metabolism in the context of obesity and may therefore be a good candidate for new microbiota-therapeutic approaches to prevent or treat metabolic diseases. Video Abstract